2023
DOI: 10.46542/pe.2023.232.144148
|View full text |Cite
|
Sign up to set email alerts
|

Profile of online drug purchasing in marketplace by students at a Faculty of Medicine and Health Sciences in Jakarta, Indonesia

Abstract: Background: Digitalisation has increased the level of expenditure on online healthcare products. Various drug categories, ranging from over-the-counter to prescription-required drugs, are available online. Currently, no data on drug purchases in the Indonesian marketplace can be found. However, data from the Indonesian Internet Service Providers Association (APJII) in 2019 shows that 92.1% of students are internet users. Objective: The study aimed to investigate drug purchasing trends in Jakarta, with a partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Again, the evidence is contradictory. Five studies reported that more older consumers purchased from online pharmacies (Brown and Li, 2014; Cokro and Arfenda, 2023 ; Desai et al, 2015 ; Jairoun et al, 2021 ; Soboleva et al, 2022 ), whereas three studies found the opposite ( Szekely et al, 2015 ; Van Buskirk et al, 2016 ; Vera-Martínez, 2023 ). In many studies, higher education was associated with increased purchase (e.g., Rajamma and Pelton, 2009 ; Brown and Li, 2014 ; Szekely et al, 2015 ; Roblek et al, 2018 ); however, Jairoun et al (2021) found that consumers with less education were more likely to purchase medicine online.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Again, the evidence is contradictory. Five studies reported that more older consumers purchased from online pharmacies (Brown and Li, 2014; Cokro and Arfenda, 2023 ; Desai et al, 2015 ; Jairoun et al, 2021 ; Soboleva et al, 2022 ), whereas three studies found the opposite ( Szekely et al, 2015 ; Van Buskirk et al, 2016 ; Vera-Martínez, 2023 ). In many studies, higher education was associated with increased purchase (e.g., Rajamma and Pelton, 2009 ; Brown and Li, 2014 ; Szekely et al, 2015 ; Roblek et al, 2018 ); however, Jairoun et al (2021) found that consumers with less education were more likely to purchase medicine online.…”
Section: Resultsmentioning
confidence: 99%
“…The studies included in this review reveal that the availability of various drug products and more options ( Little et al, 2020 ; Cokro and Arfenda, 2023 ), wide-spread availability ( Tang et al, 2023 ), and 24-h availability ( Tang et al, 2023 ) were primary motivators for purchasing medication online. Unavailability in the local market ( Abanmy, 2017 ; Bowman et al, 2020 ) and drugs not for sale in a country ( Koenraadt and van de Ven, 2018 ) were also positively related to increased purchase behavior.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Indonesia, a study on health content access behaviour stated that 95.56% of 674 respondents sought online drug information (Kristina et al, 2019). Another survey on health students in Jakarta stated that they often purchase medicines in the marketplace, including prescription-required medicines (Cokro et al, 2023). Growing concern about online drug selling has led the Indonesian government to draw up BPOM regulation No.…”
Section: Introductionmentioning
confidence: 99%